Pertimbangan Hakim Dalam Perwalian Harta Waris Penyandang Autis - Ditta Aulina Bakara; Erlina Bachri (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
Article 28B, Paragraph 2 of the 1945 Constitution explains that every child has the right to survival, growth, and development, as well as the right to protection from violence and discrimination. Not all children are born perfectly; some are born imperfect. One example is a child with a disability, such as autism. Nevertheless, they possess the right to receive education, healthcare, and freedom of expression. Additionally, children also have the entitlement to preserve their cultural and religious identity and engage in social, cultural, and political aspects of life without facing discrimination. Their rights go beyond just receiving protection; they also have the right to inherit assets in accordance with their entitlement. The purpose of this study is to identify the factors that necessitate the inheritance of these assets and to explore how judges consider the guardianship of inheritance for individuals with autism, based on decision number 121/Pdt.P/2023/PN.Tjk. The research methodology employs a normative juridical approach, involving the examination of applicable laws and regulations. Additionally, an empirical approach is used, involving on-site observations and interviews to address research-related issues. The results of this study indicate that the factors driving the need for inheritance representation stem from the fact that the petitioner's child is a minor and has a mental disability, namely autism. This is grounded in Article 330 of the Civil Code. Consequently, the appointment of a guardian is necessary to sell one of the assets left by the deceased husband, in order to finance the medical treatment of the petitioner's child with autism or mental disability. Furthermore, in deciding this case, the judge considers that pursuant to Article 360 of the Civil Code, the appointment of a guardian is deemed necessary based on requests from blood relatives of the underage child, creditors, or other relevant parties to ensure the continuity of the trial process.